Toxicological Responses of Confused Flour Beetle, Tribolium confusum du Val (Coleoptera: Tenebrinoidea) to Various Plant Essential Oils - Demirel, N.; Sener, O.; Arslan, M.; Uremis, I.; Uluc, F.T.; Cabuk, F. (Asian Journal of Chemistry, 2010)
The confused flour beetle, Tribolium confusum du Val (Coleoptera: Tenebrionidae), is one of the most serious pests of stored cereals and processed cereal products. The essential oils obtained from rosemary (Rosmarinus officinalis L.), common thyme (Thymus vulgaris L.), common sage (Salvia officinalis L.), oregano (Origanum syriacum L), Turkish oregano (Origanum onites L.), sweet marjoram (Origanum majorana L.), Greek oregano (Origanum vulgare L.) and mountain oregano (Origanum minutiflorum L.) have been analyzed by GC and GC-MS and tested for their toxicological effects against the confused flour beetle. In the current studies, γ-terpinene and p-cymene from oregano, p-cymene from common thyme, β- thujone, 1,8-cineole and L-camphor from common sage, 1,8-cineole and camphor from rosemary, carvacrol from Turkish oregano, carvacrol and thymol from sweet marjoram, carvacrol and p-cymene from Greek oregano and mountain oregano have been identified as the main volatile components. The essential oil extracted from rosemary, sweet marjoram and common thyme caused significant mortality on the confused flour beetle. In addition, rosemary had the lowest lethal concentrations (LC50: 1.12, 0.598) in both bioassays. The common thyme and sweet marjoram had followed it as a second lower lethal concentration. Therefore, the essential oils extracted from rosemary, sweet marjoram and common thyme can be recommended as a potential source of environment-friendly botanical insecticide in control of the confused flour beetle. However, essential oil extracted from Turkish oregano, Greek oregano and mountain oregano had the lowest mortality while the higher lethal concentration. Therefore, they can not be suggested for controlling of the confused flour beetle in the stored products.